Assessment of Prescribing Pattern of antibiotics by Dentists in Ardabil city Based on the International ATC/DDD System - Mehrnoosh Kaviani; Mouhamad Hassan Pourrashid; Saeedeh Galledar (Journal of Ardabil University of Medical Sciences)
Background: Antibiotics are commonly prescribed drugs by dentists. Irrational use of these drugs can lead to unwanted drug side effects, such as drug resistance in addition to unnecessary costs. This research was conducted to determine the antibiotic prescription pattern by dentists of Ardabil City based on the international ATC/DDD system. Methods: In this cross-sectional descriptive study, 250 prescriptions of patients referred to dentists in Ardabil during the second quarter of 2021 were examined. The information related to prescribed drugs includes: drug dose, frequency of drug use, number of drugs that were collected and completed in the dental offices and clinics of Ardabil city, and finally after converting the data into a certain daily dose based on the ATC-DDD system, acquired data was analyzed using One-way analysis of variance and Tukey's post hoc tests and SPSS version 21 software, the significance level was considered less than 0.05. Results: Out of the total 250 reviewed prescriptions, 207 prescriptions (82.8%) contained antibiotics. Metronidazole (73.4%) and amoxicillin (70.5%), were the most antibiotic drugs prescribed by Ardabil dentists respectively. In all prescribed drugs, the DDD value was higher than the standard DDD value. There was no significant difference between men and women in terms of the number of copies (p<0.05). The highest frequency was related to the prescription of three drugs and the lowest frequency was related to the prescription of six drugs. In terms of pharmaceutical forms, 201 prescriptions (97.1%) were only oral drugs and 6 (2.9%) were both oral and injectable Conclusion: The results showed that the amount of antibiotics prescribed in prescriptions was higher than the standard DDD and the number of drugs prescribed in prescriptions was also higher than the figure recommended by the World Health Organization.